2013
DOI: 10.1016/j.carj.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Multidetector Row Computed Tomography before Bronchial Artery Embolization in Patients with Hemoptysis: A Prospective Study

Abstract: MDCT enables detection and depiction of all bronchial and nonbronchial systemic arteries causing hemoptysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 17 publications
(19 reference statements)
5
22
0
1
Order By: Relevance
“…However, the resolution is not high enough to identify culprit BAs exactly. Based on the development of image quality, several reports have shown that MDCT angiography adequately provides the detection and depiction of both abnormal BAs and NBSAs [11,[14][15][16][17][27][28][29]. Our ndings seem to be consistent with Li et al (2019) who found that the rate of agreement between MDCT angiography and BAE in the diagnosis of arterial abnormalities was as high as 98.8% [17].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the resolution is not high enough to identify culprit BAs exactly. Based on the development of image quality, several reports have shown that MDCT angiography adequately provides the detection and depiction of both abnormal BAs and NBSAs [11,[14][15][16][17][27][28][29]. Our ndings seem to be consistent with Li et al (2019) who found that the rate of agreement between MDCT angiography and BAE in the diagnosis of arterial abnormalities was as high as 98.8% [17].…”
Section: Discussionsupporting
confidence: 86%
“…In patients with hemoptysis, the identi cation of sources and causes of bleeding with non-invasive methods prior to interventional techniques is essential. To date, there have been many studies reporting that multidetector computed tomography (MDCT) angiography before BAE plays a critical role in the diagnosis of abnormal arteries and the hemoptysis cause [9][10][11][12][13][14][15]. Importantly, it effectively identi es origins and courses of ectopic BAs and NBSAs, which should be useful for the management of this disease [8,9,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…37 In a separate study of 722 patients with minor and massive hemoptysis, a new diagnosis of malignancy was made in Multidetector CT scan is superior to chest radiograph in ability to identify both the anatomic origin and underlying cause of hemorrhage and to define the course of both bronchial and nonbronchial collateral arteries. 37,38,41,42 In a retrospective study, CT scan identified the location and cause of bleeding in 70% and 77% of cases, respectively. 37 In a comparative retrospective study of 400 patients with hemoptysis, Khalil et al 43 observed that patients who underwent multiple detector CT angiography prior to BAE were more likely to have successful resolution of hemorrhage from embolization and were also less likely to need emergent surgery.…”
Section: Pathophysiologymentioning
confidence: 99%
“…In the last few years, several works have recommended multidetector computed tomography angiography (MDCT-A) before BAE, although not specifically in patients with CF. This approach enables detection of the source of bleeding in 63%e100% of cases before treatment [3,4]. We report a case that illustrates the value of MDCT-A for localization of aberrant bronchial arteries before treatment.…”
Section: To the Editormentioning
confidence: 94%